2004
DOI: 10.4141/s03-058
|View full text |Cite
|
Sign up to set email alerts
|

Influence of compost on the physical properties and organic matter fractions of a fine sandy loam throughout the cycle of a potato rotation

Abstract: . 2004. Influence of compost on the physical properties and organic matter fractions of a fine sandy loam throughout the cycle of a potato rotation. Can. J. Soil Sci. 84: 211-218. Potato (Solanum tuberosum L.) rotations often require organic amendments to maintain or improve soil organic matter levels and soil physical properties. However, beneficial effects of compost can be modified by time of application and rotating tillage depth and intensity. This study was conducted to evaluate the effect of compost app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 25 publications
4
35
0
6
Order By: Relevance
“…However, on the basis that soilmoisture status and other soil physical attributes may benefit from cumulative organic amendment (Russell 1973), a measure of the earlier 2-yr segment and of the latter 2-yr segment of the experiment showed striking differences related to soil compaction, showing about a 50% reduction in TO and PR, and potato tuber yield showing a 30% weight increase. The significant increase in crop yield shown in Table 2 with compost has met traditional expectations and conforms to yield increases reported by Carter et al (2004). And, although this study cannot make specific attributions, it identified important relationships based on established, fundamental principles (Mitchell 1970;Russell 1973) that increased crop yield could be enabled by improved soil physical condition Á particularly essential to the below-ground development of any crop whether in the form of roots, tubers or rhizomes.…”
Section: Phasesupporting
confidence: 75%
See 1 more Smart Citation
“…However, on the basis that soilmoisture status and other soil physical attributes may benefit from cumulative organic amendment (Russell 1973), a measure of the earlier 2-yr segment and of the latter 2-yr segment of the experiment showed striking differences related to soil compaction, showing about a 50% reduction in TO and PR, and potato tuber yield showing a 30% weight increase. The significant increase in crop yield shown in Table 2 with compost has met traditional expectations and conforms to yield increases reported by Carter et al (2004). And, although this study cannot make specific attributions, it identified important relationships based on established, fundamental principles (Mitchell 1970;Russell 1973) that increased crop yield could be enabled by improved soil physical condition Á particularly essential to the below-ground development of any crop whether in the form of roots, tubers or rhizomes.…”
Section: Phasesupporting
confidence: 75%
“…Biowaste amendments can be expected to improve the physical condition of degraded soil via the soil organic matter ''pool'' (Ambus and Jensen 1997;Angers and Recous 1997;Beyer et al 1999;Carter et al 2004), and are historically credited with giving yield increases particularly in small-scale farming operations. However, one may question (a) the capacity of these operations to use all of the potentially available biowaste, and (b) the feasibility of ramping-up, to commercial-scale, biowaste usage in this region.…”
mentioning
confidence: 99%
“…Field capacity and available water holding capacity (AWC, pF 1.8 -4.2) are generally influenced by the particle size, structure and content of OM. Several studies confirm a significant, positive impact of OM amendment to soils on FC (Evanylo et al, 2008;Tejada et al, 2006;Carter et al, 2004). Amongst others, this effect results from the improved formation of secondary pore structures which can be mainly ascribed to root and animal tubes.…”
Section: Increase Of Aggregate Stabilitymentioning
confidence: 88%
“…Organic matter applied by compost improves water conductivity of soils (Carter et al, 2004) by providing a food source for soil organisms which contribute to the formation of macro-pores, in turn. Additionally, it has a direct structure-stabilizing effect for soil.…”
Section: Increase Of Aggregate Stabilitymentioning
confidence: 99%
“…Carter et al (2004) found that compost-induced benefits in soil physical properties (bulk density, macro-porosity, oxygen diffusion rate, shear vane strength, water-filled pore space) were mainly expressed in the red clover (Trifolium pretense L.) phase of a 3-yr potato-barley-red clover rotation in Prince Edward Island. Soil water content at -0.033 MPa was increased by compost in the potato phase, compared with the control.…”
Section: Maintenance Of Soil Quality and Soil Reclamationmentioning
confidence: 99%